QoS Support with Taguchi Method in Simulation Modeling Hybrid Architecture of Optical and Multi-Hop Wireless Ad Hoc Networks - A. Wong, M.; Jamel Elias, Shamsul; Mahdaliza Idrus, Sevia; Zulkifli, Nadiatulhuda; Iqbal, F. (International Journal of Engineering and Technology, 2018)
Majority of the resource consumption is consumed for their operation in the access network of mobile wireless part because of its dynamic topology and limited range of each mobile host's wireless transmissions. This paper presents a technique using OMNeT++ software for building a design of experiment simulation model with Taguchi optimization method supported mobile circumstantial network (MANET) of AODVUU communication protocol to be apply into collaborate multiple layers framework of deploy over passive optical network (PON) referred to as the walk Mobile Hybrid optical wireless access network (erL-MMHOWAN). it's to guage the network quality of service effectively that take into account variety of nodes over that the Edouard Manet could operate. Its performance is examined on the known performance metrics just like the network capability and energy consumption. Simulation result shows for the random mobile property during this convergence of heterogeneous optical wireless network will perform higher with the optimized front-end wireless circumstantial.
Keywords: mobile ad hoc network; Last Mile Mobile Hybrid optical wireless access network; design of experiment; network capacity; energy consumption; taguchi. .